2015
DOI: 10.1097/cej.0000000000000098
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin and NSAIDs for breast cancer chemoprevention

Abstract: Novel treatment strategies are needed for breast cancer chemoprevention. Tamoxifen is the only drug approved for the chemoprevention of estrogen receptor-positive breast cancer. However, to date, no treatment exists for the chemoprevention of estrogen receptor-negative breast cancer. NSAID use is associated with a reduced risk of breast cancer. However, the biological mechanisms underlying the effect of NSAID on breast cancer are not well defined. NSAIDs inhibit cyclooxygenases, thus preventing the formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…For instance, one postulated inflammation-related mechanism for breast cancer is upregulation of cyclooxygenase 2 (COX2) and its product, prostaglandin E2 (PGE), which results in increased aromatase expression in adipose tissue and increased conversion of androgen precursors to estrogens [77,78]. In this regard, the use of some non-steroidal anti-inflammatory drugs has been associated with a reduced risk of estrogen receptor (ER)-positive BC incidence or recurrence [79,80,81,82,83,84,85]. …”
Section: Functional Pathwaysmentioning
confidence: 99%
“…For instance, one postulated inflammation-related mechanism for breast cancer is upregulation of cyclooxygenase 2 (COX2) and its product, prostaglandin E2 (PGE), which results in increased aromatase expression in adipose tissue and increased conversion of androgen precursors to estrogens [77,78]. In this regard, the use of some non-steroidal anti-inflammatory drugs has been associated with a reduced risk of estrogen receptor (ER)-positive BC incidence or recurrence [79,80,81,82,83,84,85]. …”
Section: Functional Pathwaysmentioning
confidence: 99%
“…But the exact mechanisms of aspirin that exert its anti-tumor effect are yet to be elucidated [21, 26]. Studies have reported that aspirin and its primary metabolite salicylic acid both have the ability to decrease the mRNA and protein levels of c-myc in human colon cancer cell lines, which might be one of the mechanisms for the antineoplastic activity [27, 28].…”
Section: Introductionmentioning
confidence: 99%
“…Inactivating COX‐2, that has been found to be overexpressed in breast cancer tissue when compared to normal tissue, may reduce the downstream synthesis of pro‐inflammatory prostaglandins (PG), particularly PGE 2 , a potent mitogen. This reduction results in inhibition of angiogenesis, proliferation and in the promotion of apoptosis . There is also accumulating evidence that the inhibition of COX‐2 and PGE 2 is associated with the suppression of estrogen synthesis via a decrease in aromatase activity .…”
Section: Discussionmentioning
confidence: 98%